The tectonic evolution of Lake Eğirdir, West Turkey - Karaman, M. Erkan (Geologos, 2011)
Lake Eğirdir is one of the most important fresh-water lakes of Turkey. It has a tectonics-related origin. The area formed under a roughly N-S compressional tectonic regime during the Middle Miocene. The stresses caused slip faults west and east of Isparta Angle, and the lake formed at the junction of these faults. The area subsided between normal faults, thus creating the topographic condition required for a lake. The lacustrine sediments have fundamentally different lithologies. After the Late Miocene, central Anatolia started to move westwards, but western Anatolia moved in a SW direction along the South-western Anatolian Fault, which we suggest to have a left lateral slip, which caused that the Hoyran Basin moved t7 km towards the SW and rotated 40° counterclockwise relative to Lake Eğirdir.